2017
DOI: 10.1371/journal.pone.0173836
|View full text |Cite|
|
Sign up to set email alerts
|

Translocation of the neonicotinoid seed treatment clothianidin in maize

Abstract: Neonicotinoid seed treatments, typically clothianidin or thiamethoxam, are routinely applied to >80% of maize (corn) seed grown in North America where they are marketed as a targeted pesticide delivery system. Despite this widespread use, the amount of compound translocated into plant tissue from the initial seed treatment to provide protection has not been reported. Our two year field study compared concentrations of clothianidin seed treatments in maize to that of maize without neonicotinoid seed treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 44 publications
(75 reference statements)
4
71
0
Order By: Relevance
“…Although additional sites/years with variable patterns of rainfall would likely exhibit some variability in foliage concentrations, our data showing a relatively limited efficacy window are supported by our 2013 yield analyses and suggest that it is unlikely that neonicotinoid insecticides applied as seed treatments will provide significant protection against soybean aphid populations without additional foliar insecticide applications later in the season. A similarly rapid decrease of in‐plant concentrations of the neonicotinoid clothianidin was recently reported in field‐grown corn (maize) plants, providing further evidence that the high water solubility of neonicotinoids is likely to limit their longevity on or near plants in the field . The pest management window offered by seed treatments has been investigated in soybeans in the past: McCornack and Ragsdale demonstrated that in a field bioassay aphid mortality persisted for up to 49 days after planting, although this study noted that older leaves exhibited higher thiamethoxam concentrations based on aphid mortality.…”
Section: Discussionmentioning
confidence: 56%
“…Although additional sites/years with variable patterns of rainfall would likely exhibit some variability in foliage concentrations, our data showing a relatively limited efficacy window are supported by our 2013 yield analyses and suggest that it is unlikely that neonicotinoid insecticides applied as seed treatments will provide significant protection against soybean aphid populations without additional foliar insecticide applications later in the season. A similarly rapid decrease of in‐plant concentrations of the neonicotinoid clothianidin was recently reported in field‐grown corn (maize) plants, providing further evidence that the high water solubility of neonicotinoids is likely to limit their longevity on or near plants in the field . The pest management window offered by seed treatments has been investigated in soybeans in the past: McCornack and Ragsdale demonstrated that in a field bioassay aphid mortality persisted for up to 49 days after planting, although this study noted that older leaves exhibited higher thiamethoxam concentrations based on aphid mortality.…”
Section: Discussionmentioning
confidence: 56%
“…The decline in non‐target effects over time was likely linked to the decreasing titer of clothianidin in the plants. Recent work determined that clothianidin concentrations in plant tissue (root and seedling) decline rapidly in the first 20 days after planting, with less than 1.5% of the applied clothianidin being taken up by the plant . Little is known about the environmental fate of the remaining 98% of the active ingredient; however, there is evidence that much of it is lost to ground and surface water .…”
Section: Discussionmentioning
confidence: 99%
“…Recent work determined that clothianidin concentrations in plant tissue (root and seedling) decline rapidly in the first 20 days after planting, with less than 1.5% of the applied clothianidin being taken up by the plant . Little is known about the environmental fate of the remaining 98% of the active ingredient; however, there is evidence that much of it is lost to ground and surface water . Even shortly after planting, when the initial soil concentrations of clothianidin are the highest, studies have indicated a low risk to non‐target invertebrates because the expected environmental soil concentrations are lower than the no‐observed effect concentration for the most sensitive tested species.…”
Section: Discussionmentioning
confidence: 99%
“…5). A maximum of 1.34% of the initial clothianidin seed treatment was taken up by corn seedlings (Alford and Krupke, 2017). The seeds had a great affinity for coumarin 120 uptake when a small amount was available.…”
Section: Discussionmentioning
confidence: 99%